Paraoxonase and Arylesterase Activities in Patients with Rheumatoid Arthritis - Özlem Altındağ,; Mehmet Karakoç,; Neslihan Soran,; Hakim Çelik,; Necla Çelik,; Şahabettin Selek, (Archives of Rheumatology, 2007)
Objective: The aim of the study was to evaluate serum paraoxonase (PON) and arylesterase (ARE) activities as well as lipid hydroperoxide (LOOH) levels in patients with rheumatoid arthritis (RA). We also investigated serum total antioxidant status (TAS) and total oxidative status (TOS) to reveal whether there is an association between the PON/ARE activities and oxidative stress. Our hypothesis is that PON and ARE activities which related to the risk of developing coronary artery disease are low in RA patients. Patients and Methods: Twenty-five patients with RA and 26 healthy controls were included in the study. Serum PON and ARE activities were measured spectrophotometrically. LOOH levels were measured by ferrous oxidation with xylenol orange assay. TAS, TOS levels were determined by using a novel automated methods. Results: Paraoxonase and arylesterase activities were significantly lower in patients with RA, LOOH levels were significantly higher (p<0.001, p =0.02, p =0.006, respectively) in patients with RA than in healthy controls. In patients with RA, serum TOS was higher and serum TAS was lower when compared with those of healthy controls (p < 0.001). PON was negatively correlated with LOOH (r = -0.356, p = 0.01), ARE was positively correlated with TAS (r = 0.429, p = 0.002), LOOH was negatively correlated with TAS (r = -0.585, p = 0.001). Conclusion: Our results show that PON and ARE activities, which have antiatherogenic capability, are decreased in patients with RA. PON and ARE activities may be affected by oxidative stress which contribute to the pathogenesis of RA. (Rheumatism 2007; 22: 132-6)